Reporting Adverse Drug Events in Drug Administration Process among Nursing Personnel - Katarzyna Kwiecień-Jaguś; Klaudia Paluch; Anna Małecka-Dubiela; Wioletta Mędrzycka-Dąbrowska; Monika Kopeć (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Adverse events (AE) in the process of pharmacotherapy can have direct consequences on the health and life of a patient. Factors leading to AE are categorized in human and systematic ones. Among the latter ones, the most important are significant shortages of nursing staff as well as stress, fatigue and the Occupational Burnout Syndrome. Reporting of AE is a crucial pillar of prevention of adverse events in drug administration in nursing.